Criminal Sanctions Against Money Laundering Crimes in the Perspective of Economic Analysis of Law - Fauzi Yunandi; Arrum Budi Leksono (Rechtsnormen: Journal of Law, 2023)
Background. Money laundering as a crime in the economic sphere shows that crime is a consequence of economic activity and sustainable development, which is a challenge for the state. Money laundering is the disguise or attempt to disguise the origin of profits from illegal or legitimate activities. Purpose. The purpose of this research is to analyze the money laundering law "criminal sanctions against money laundering crimes" from the point of view of economic analysis. Method. The research was carried out using a normative juridical approach and an empirical approach. The data used in this study were secondary data obtained from library materials, and field research was carried out by observation and interviews (interviews). The data obtained were analyzed qualitatively and juridically and deductively concluded. Results. The use of Bitcoin as a money laundering tool is rapidly increasing worldwide with the development of technology and Industry 4.0, according to Dean Ediana Ray, Director of the Financial Transaction Reports and Analysis Center (PPATK). In Indonesia, money laundering was initially regulated under Law No. 8 of 2010 on the Prevention and Eradication of Money Laundering. Conclusion. The normative legal approach focuses on analyzing legal normative systems such as principles, norms, legal rules, court decisions and principles.